Selective control of Rhipicephalus (Boophilus) microplus in fipronil-treated cattle raised on natural pastures in Lages, State of Santa Catarina, Brazil - Paim,Fernanda (2011)
An examination of a selective control of Rhipicephalus (Boophilus) microplus and consequent cost reduction was carried out in two areas of native pasture in the municipality of Lages, State of Santa Catarina, Southern Brazil, from May 2007 to April 2009. Forty cattle were divided into two groups of 20 animals each (conventional and selective control groups). At 14-day intervals female ticks larger than 4.5 mm found on the right flank of cattle bodies were counted, and these results multiplied by two. Fipronil 1 mg.kg-1 pour on was then administered for tick control. In the conventional group all the cattle were treated when tick count averaged more than 40 female ticks per animal while in the selective group only animals parasitized by more than 40 ticks were treated with acaricide. Every 28 days the cattle's weight was checked for cost-effective analysis. The conventional group required an additional 20 doses of fipronil compared with the selective one. There was no statistically significant differences regarding weight gain in both groups.